Analisa Penjualan Air Minum dalam Kemasan dengan Metode Single Exponential Smoothing - Retno Tri Vulandari; Andriani Kusumaningrum; Dwi Handoko (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2022)
The bottled consuming water enterprise has grown rapidly to diverse provinces and cities in the course of Indonesia now. The development of this enterprise is because of high call for clients and the lower nice of uncooked water in springs and wells PT. Cahaya Bumi Intanpari (CBI) is a agency that produces gallons, bottles, and glasses bottled drinking water beneath the logo â€œAirMuâ€. sales of bottled water every month constantly vary, the control of PT. Cahaya Bumi Intanpari calls for an estimate of the quantity of manufacturing of each type of bottled water to marketplace demand within the destiny. based totally at the description of the history, in this take a look at, a computing device-based application became designed and built. The research method used consists of information series and statistics analysis, statistics series includes remark, interviews, and literature have a look at, whilst statistics evaluation consists of making facts waft diagrams. The forecasting version is used in forecasting the income of bottled drinking water at PT. Cahaya Bumi Intanpari is a time series or it may be referred to as a time collection, and the forecasting technique used is unmarried exponential smoothing. From the outcomes of calculation checking out, it's far demonstrated that the single exponential smoothing method can be applied inside the AMDK income forecasting system, primarily based on the validity take alook at, itâ€™s miles discovered that the prediction check effects of bottled consuming water sales below 20% are covered within the appropriate standards.